2021
DOI: 10.1002/psp.2523
|View full text |Cite
|
Sign up to set email alerts
|

Worse life, psychological suffering, but ‘better’ housing: The post‐gentrification experiences of displaced residents from Xuanwumen, Beijing

Abstract: Gentrification, the process of transforming a neighbourhood with social class upgrading and landscape change, has undoubtedly impacted existing residents. Although massive amounts of research have analysed gentrification‐induced displacement, there is comparatively much less research about the residents' experiences after being displaced. Therefore, this paper seeks to fill this gap through empirical research on the subjective experiences of displaced residents from Xuanwumen, Beijing. The study finds that tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…206-210) identified that a significant proportion of low-income households leave the city and relocate to cities with weaker economies and a more affordable housing stock. This finding by Van Criekingen is consistent with more recent studies which stress that displaced households relocate out of the city, to the suburbs (Sink & Ceh 2011;Weller & Van Hulten 2012;Sturtevant 2014;Mah 2021;Huang & Liu 2022), and satellite towns in the metropolitan region (Hochstenbach & Musterd 2018. It is apparent that claims regarding the suburbanization of poverty generally correspond to more recent research compared with those claiming that displacees move within the surrounding area.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…206-210) identified that a significant proportion of low-income households leave the city and relocate to cities with weaker economies and a more affordable housing stock. This finding by Van Criekingen is consistent with more recent studies which stress that displaced households relocate out of the city, to the suburbs (Sink & Ceh 2011;Weller & Van Hulten 2012;Sturtevant 2014;Mah 2021;Huang & Liu 2022), and satellite towns in the metropolitan region (Hochstenbach & Musterd 2018. It is apparent that claims regarding the suburbanization of poverty generally correspond to more recent research compared with those claiming that displacees move within the surrounding area.…”
Section: Resultssupporting
confidence: 89%
“…These articles rely on primary data. Representative articles of this pole of the literature include Kleinhans (2003) and Huang and Liu (2022). The second dimension (vertical axis Figure 3A) of the MCA opposes articles focusing on gentrifiers and their residential trajectories to articles focusing on the trajectories of displacees.…”
Section: Multivariate Analysis Of the Corpus -Tomentioning
confidence: 99%
“…The social influence of gentrification-a major research topic in critical geography-has risen greatly in recent years. Increasingly, research has begun to focus on how gentrification excludes ethnic minority groups and other disadvantaged groups (Sakzlolu and Lees, 2020;Huang and Liu, 2022). Both commercial gentrification and residential gentrification are generally seen as squeezing the survival space for original residents and traditional industries by driving retail shop/house prices higher, forcing outward migration (Gonzalez and Waley, 2003;Zukin, 2008;Ferm, 2016;Song et al, 2020), and destroying the authenticity of the city (Martinez, 2016).…”
Section: Emerging Consumption Commercial Gentrification and Urban Changementioning
confidence: 99%
“…Overall, past research reveals the impact of built environment quality on RS and people's perceptions of such characteristics in the context of meeting their cognitive and emotional requirements and expectations [13][14][15][16][17]. Little research has been conducted on the relationship between these factors and mining-affected families' QoL, which is affected by resettlement as a form of compensation for their displacement to make way for large-scale mining projects [11,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%